The predictive value of PSMA PET/CT in determining pathological upgrading of prostate cancer: A pooling up analysis - Liu, Yue; Qu, Shu-Pei; Zhai, Ling-Yun (Frontiers in Oncology, 2025)
PurposeThe issue of pathological upgrading following radical prostatectomy poses a significant challenge for urologists, and prostate-specific membrane antigen (PSMA) positron emission tomography-computed tomography(PET/CT) has gained increasing prominence as a preoperative assessment tool for patients with prostate cancer in recent years. This study aims to assess the diagnostic accuracy of PSMA PET/CT in predicting pathological upgrading after radical prostatectomy.MethodsWe conducted a meta-analysis of diagnostic studies using data from the Cochrane CENTRAL, PubMed, Embase, Scopus, and Web of Science databases through March 2024. We strictly adhered to the guidelines outlined in the PRISMA statement for conducting this diagnostic meta-analysis. We computed the pooled diagnostic accuracy and evaluated heterogeneity while exploring potential sources of heterogeneity through subgroup analysis.ResultsA total of 7 studies involving 507 patients were included in the final analysis. All participants had biopsy-confirmed prostate cancer and underwent radical prostatectomy. Prior to surgery, all patients underwent PSMA PET/CT imaging. The pooled diagnostic accuracy yielded a sensitivity of 0.68 (95% CI, 0.60 - 0.76) and specificity of 0.74 (95% CI, 0.59 - 0.85). The area under the summary receiver operating characteristic curve was calculated as 0.74 (95%CI, 0.70 - 0.78). Although heterogeneity was observed, its source remained unclear.ConclusionThe PSMA PET/CT demonstrates a moderate level of accuracy in predicting pathological upgrading following radical prostatectomy, making it a tool with potential clinical application value, particularly in the field of radiotherapy. However, further studies are warranted to enhance its relevance and applicability.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024503406.